Incorporating Fatwa Validation Clause in Sukuk Legal Documentations: A Tool for Shariah Risk? - Dr Hakimah Yaacob; Syeikh Dr Essam Ishaq; Dr Kamaru Salam Yusof; Abdul Hadi bin Abdul Satar (IJUS | International Journal of Umranic Studies, 2022)
Sukuk is the most disputable structures with complicated issues of Shariah being litigated in courts. Over reliance on the brief Shariah pronouncement may cause uncertainty of legal standing. This paper is an attempt to justify factors on the importance of incorporating Fatwa Validation Clause into the legal documentations. The objective is to look into the materiality of fatwa validation clause in sukuk documents. This paper employs library research. The findings led to several observations where cases decided in England High Court indicates alarming signals on the fate of shariah documentations. In addition, Several jurisdictions refused to recognise shariah contracts due to absence of enabling legal environment. Furthermore, the borderless transactions in finance has led to incorporate the lex mercatoria of trade into their legal documentations. The litigants have been trying to merge out their autonomy over the contract by stipulating terms and clauses that works in their favor. However, to some extent, the struggles shrinked by the legal framework derecognised their intended values. The paper concludes with several recommendations for future consideration.